ARCHITECTURAL ECOLOGY OF CIVIL BUILDINGS AND STRUCTURES - Zhovkva, Olga (Theory and practice of design, 2024)
Energy efficiency and environmental friendliness, as important principles of sustainability for multifunctional complexes, are here considered in the context of the international experience, enabling an identification of the main aspects that are applicable when designing such buildings in Ukraine. Purpose: The purpose of this article is to study the principles of improving energy efficiency and environmental friendliness of multifunctional complexes in Ukraine and thereby enrich the national experience in designing sustainable architecture. Results: On the basis of the study, scientific principles and recommendations are developed that contribute to improving the energy efficiency and environmental friendliness of such complexes. Conclusion: It is concluded that the use of alternative energy sources can cover at least 15–20% of the total energy consumption, and by optimizing the plan it is possible to increase the energy efficiency of a building by up to 14%. Goal. In this regard, this research is aimed at the study of world experience in the design of energy-efficient sustainable complexes with mixed functions, the development of project proposals aimed at achieving energy efficiency and environmental friendliness, and the development of scientific principles of energy efficiency in architecture. Methodology. In the course of the research, the field survey method, grapho-analytical method, etc. were widely used. The results. the issue of designing energy-efficient and ecological buildings was investigated; issues of interaction between volumetric and spatial forms and energy- saving technologies; methods of using renewable energy sources; the question of the influence of the shape of the building on energy efficiency, etc. Scientific novelty. Scientific principles of energy efficiency in the architecture of public buildings and structures are proposed. Practical significance. The results of the research can be applied in project practice, scientific work, and teaching activities.